Low-flammable electrolytes with fluoroethylene carbonate based solvent mixtures and lithium bis(trifluoromethanesulfonyl)imide for lithium-ion batteries. (1st March 2019) - Wang, Zhengqi; Hofmann, Andreas; Hanemann, Thomas
Abstract: Here we report a series of electrolyte mixtures containing lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and fluoroethylene carbonate (FEC) based solvents for improving the flame-resistance of electrolyte solvents compared to state-of-art carbonate based electrolytes. Physical, rheological and conductive properties of the different mixtures are measured. These results give insight into the interaction of the ions and molecules such as ionic dissociation, solvation and diffusion. Aluminum anodic dissolution caused by the conducting salt is studied in Li||Al cells. This corrosion effect could be successfully removed using the additive lithium bis(oxalato)borate. The electrochemical performances in half cell (Li||NMC) and full cell (C||NMC, in form of coin and pouch-bag) are demonstrated and the cycling ageing of the electrolytes as well as the growth of the resistive interface layers are reflected by impedance measurements on the cycles. These results are related to the ion transport in solution. To achieve a balance of the various properties necessary for the battery performances, a low-flammable electrolyte is chosen as a promising alternative in case of the safety and capacity retention improvement.